Strategi dan Usaha Reservasi untuk Meningkatkan Tingkat Hunian di Grand Orchid Hotel Yogyakarta - Krestanto, Hery (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2019)
This study aims to determine the strategy and reservation effort to increase occupancy rates at the Grand Orchid Hotel Yogyakarta. This research was conducted at the Grand Orchid Hotel in Yogyakarta.The type of data collected in this study is qualitative, namely the strategy and reservation effort to increase occupancy rates at the Grand Orchid Hotel Yogyakarta. The data analysis technique used is the direct observation method, direct interview. The results of the research obtained are that reservations have a very important role to increase occupancy rates and there are things that support to increase occupancy rates are complete room facilities, strategic hotel location, intensity of promotion, good employee service.